Kritik atas Kurikulum dan Buku Ajar Bahasa Arab SD/MI Kelas VI - Ridwan, Muhammad Mahfud (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
The curriculum is an important element in education. Derived from the Latin word curir which means runners; and curere which means the place encouraged. Technically, the curriculum means that the distance that must be taken by the runner. In the context of education, the curriculum is an âarenaâ learn to master certain subjects. Textbooks are one of the means to reach the finish line set curriculum. Quality curriculum and textbooks are good and supported by competent teachers will produce a quality education. This short article containing criticism of kurikulun and textbooks Arabic Class VI SD / MI.